Development of human-computer interface based cursor control application - Ng, Chek Yong (2014)
The objective of the project is to design and develop a computer mouse cursor application that is controlled by Brain Computer Interface (BCI). Steady State Visual Evoked Potentials (SSVEP) is the type of BCI to be implemented. With this BCI controlled cursor, users will be able to perform simple tasks on a computer screen.